Literature Review of Research Trends in The Development of Computer-Based Physics Interactive Learning Media for High School Students in 2020-2025 - Harlia Ningrum, Nabila Triska; Subali , Bambang (Indonesian Journal of Science and Education, 2025)
This study aims to identify trends in research on the development of interactive computer-based physics learning media for high school students in 2020–2025. The method used is a Systematic Literature Review (SLR) with a structured approach through searching for articles in the Google Scholar and Crossref databases using specific keywords. Out of a total of 2,129 articles found, 25 articles were deemed suitable for analysis based on criteria of relevance and focus on physics education. The findings indicate that the trend in the development of computer-based interactive learning media continues to rise, with a dominance of R&D and ADDIE development methods. The media developed generally aim to enhance conceptual understanding, learning outcomes, and critical thinking skills among students. The most frequently used physics topics in media development are linear motion, Newton's laws, and waves, with diverse development applications such as Adobe Flash, Canva, Articulate Storyline, and Google Sites. These findings indicate that the integration of computer technology in physics education can overcome limitations in understanding abstract concepts, improve the quality of the learning process, and serve as an important reference for the future development of interactive digital-based learning media. Keywords: literature review, interactive learning media, physics, computer, high school